Mimicry in Ahmad Tohari's Short Stories "Paman Klungsu" and "Kuasa Peluitnya": A Postcolonial Analysis by Homi K. Bhaba - Qarimah, Aryana Nurul; Junaid , Syahruni (Linguistika Kultura, 2026)
This study aims to analyze the manifestations of mimicry and ambivalence in Ahmad Tohari's short story Paman Klungsu dan Kuasa Peluitnya (PKKP) through the lens of Homi K. Bhabha's postcolonial theory. The research method employed is descriptive qualitative, focusing on literary discourse as a documentation of colonial traces. The results indicate that the character Paman Klungsu engages in mimicry by adopting attributes of power, such as the "Poltas Swakarsa" vest and a whistle, to gain authority in public spaces. However, these actions create ambivalence; while he feels authoritative, he simultaneously experiences a split identity when confronted with local values represented by the character Yu Binah. The study concludes that the imitation performed by the colonized subject never achieves perfect mimicry of the original, and power often remains attached to physical attributes rather than the subject.